The news at the ends of the earth : the print culture of polar exploration - Blum, Hester (Duke University Press, 2019)
Hester Blum examines the rich, offbeat collection of printed ephemera created by nineteenth- and early twentieth-century polar explorers, showing how ship newspapers and other writing shows how explores wrestled with questions of time, space, and community while providing them with habits to survive the extreme polar climate.